A new species of Canace Haliday from Portugal, with a revised key to species (Diptera: Canacidae: Canacinae) - Munari, Lorenzo; Almeida, Jorge Mota (Zootaxa, 2014)
A new species of Canace Haliday, in Curtis, 1837 from Portugal is described. This species, related to C. actites Mathis, 1982, is known so far from a single maritime locality near Lisbon. A key to species of the genus is also provided.